2012
DOI: 10.1002/ptr.4669
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effect of High‐dose Isoflavones from Pueraria lobata (Willd.) Ohwi on Lipid and Bone Metabolism in Ovariectomized Mice

Abstract: We investigated the acute metabolic effects of isoflavones from Pueraria lobata (Willd.) Ohwi (IPL) in ovariectomized (OVX) mice. After 4 weeks of IPL feeding at 500 mg/day/kg body weight (OVX500), plasma 17β-estradiol concentrations were significantly higher (+25%, p < 0.05), whereas plasma triglyceride levels were significantly lower in OVX mice (-15%, p < 0.05) compared with controls. Abdominal adipose tissue weight was marginally reduced in IPL-fed groups compared with OVX controls and the plasma levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 28 publications
2
10
0
Order By: Relevance
“…However, EST mRNA levels were reduced to their nadir after ovariectomy with no change in the pollutant-exposed mice along with circulating estrogen levels reduced to low levels (data not shown). These findings are consistent with the literature indicating that EST gene expression depends on estrogen levels and that its involvement in the regulation of estrogen bioavaibility is lost in ovariectomized animals (Cho et al, 2012).…”
Section: Pollutants Enhanced E2 Signalling In the Liver In Conditionssupporting
confidence: 93%
“…However, EST mRNA levels were reduced to their nadir after ovariectomy with no change in the pollutant-exposed mice along with circulating estrogen levels reduced to low levels (data not shown). These findings are consistent with the literature indicating that EST gene expression depends on estrogen levels and that its involvement in the regulation of estrogen bioavaibility is lost in ovariectomized animals (Cho et al, 2012).…”
Section: Pollutants Enhanced E2 Signalling In the Liver In Conditionssupporting
confidence: 93%
“…From previously reports, the average amount of miroestrol in P. candollei was 8–27 μg/g dry weight (Yusakul et al, ; Yusakul, Putalun, Udomsin, Juengwatanatrakul, & Chaichantipyuth, ), while the concentration of puerarin was found to vary among plant species, e.g. P. candollei, 120–4,000 μg/g dry weight (Cherdshewasart et al, ; Cherdshewasart & Sriwatcharakul, ; Manosroi & Manosroi, ; Pongkitwitoon et al, ) and P. lobata , 75–13,000 μg/g dry weight (Cho et al, ; Udomsin et al, ). Therefore, when compared with previous reports, our developed method is the optimal sensitivity for the detection of both miroestrol and puerarin in the samples.…”
Section: Resultsmentioning
confidence: 93%
“…A number of recent reports have shown that isoflavones can ameliorate experimental menopausal symptoms. For example, Cho and Jun reported that isoflavones from Pueraria lobata inhibited the reduction of bone mineral density in the femurs of ovariectomized mice (Cho et al ., ). Another study showed that two isoflavones, i.e.…”
Section: Introductionmentioning
confidence: 97%